Evaluación de diferentes dosis y épocas de aplicación del herbicida accent (nicosulfuron) en el cultivo de maíz (zea mays l) en presencia de dos niveles de fertilización en la zona de Babahoyo Provincia de los Ríos. - Escobar Fernández, Freddy Rolando (2011)
On the grounds of the Farm "El Palmar" belonging to the Faculty of Agricultural Sciences at the Technical University of Babahoyo, located at Km 7.5 of the way Babahoyo - Montalvo, a trial was testing three doses of herbicides three times Nicosulfuron application in the presence of two levels of chemical fertilizer, maize hybrid 'Thunder NB - 7443', in order to evaluate the effects of herbicide application in different vegetative stages Accent Hybrid, identifying the time and appropriate dosage of hybrid Accent to maximize grain yield, test the response of the hybrid chemical fertilization, and economic analysis of grain yield based on the cost of treatments. The trial was conducted under the design 'randomized block' with 2 x 9 factorial arrangement in four replications. Accent herbicide doses were 40, 50 and 60 g / ha, applied at 12, 18 and 24 days after planting, in the presence of chemical fertilizer levels from 76 to 15 - 90 and 152 - 30 - 180 Kg / has NPK.